Dietetic Students’ Attitudes to and Knowledge of Working with Older People - Mackenzie, Myra; Macaulay, Connie (International Journal of Practice-based Learning in Health and Social Care, 2020)
Across the world, people are living longer but not necessarily healthier lives. Healthcare professionals will need to be prepared to work with older people, recognising that, at all stages of the lifespan, attention to nutrition and other health behaviours can impact positively on wellbeing. This study examined the attitudes, knowledge and future career preferences of pre-registration dietetic students in the United Kingdom towards working with older people. A questionnaire, based on the validated Palmore Facts on Aging Quiz and adapted to a UK population, was sent to the fifteen universities which provide dietetic courses in the UK approved by the Health and Care Professions Council (HCPC). Responses were received from thirteen universities, and, of the estimated 1250 students, 285 questionnaires were completed (response rate 23%) with the predominant demographic being 91% female, and 86% undergraduate degree type. The mean knowledge score was higher in postgraduate vs. undergraduate students (69.6% vs. 65.2%; p<0.011). A weak positive correlation (rs = 0.155) was found between number of placement weeks carried out and knowledge score (p <0.01). Care of the elderly was the least preferred of five specialities, and 65-plus was the fourth preferred age group out of five. A greater focus should be placed on the delivery of aging education and placement experiences in dietetic courses to increase the number of graduate dietetic students who have positive work preferences towards older adults.